THE RELATIONSHIP BETWEEN EMOTIONAL MATURITY AND PROBLEM-FOCUSED COPING IN GRADE XI VOCATIONAL HIGH SCHOOL STUDENTS - Fanita, Diah Ayu Nadia Nur (jfpublisher, 2025)
Introduction. Problem-focused coping is a way to overcome problems by finding and solving the root of the problem. Factors that influence problem-focused coping are age, gender, socio-economic status, and level of education. Emotional maturity is one of the appropriate actions is overcoming problem-focused coping in students or teenagers. The aim of this research was to determine the relationship between emotional maturity and problem-focused coping in class XI students at the Taruna Jaya Prawira Vocational School in Tuban. Methods. This research uses a correlational analytical method with a cross-sectional approach. The sampling method uses the Probability Sampling technique. The total sample was 153 respondents, and the instruments used were the emotional maturity variable questionnaire sheet and the problem-focused coping questionnaire sheet using Spearman's rho correlation test. Result&Analysis. The research obtained results p-value = 0.000 showed that there is a relationship between emotional maturity and problem-focused coping, with a correlation value of 0.552, namely a strong correlation in a positive direction. Discussion. Problem-focused coping approach in adolescents has become a major focus for psychologists and educators.